2007
DOI: 10.1177/0002764207306071
|View full text |Cite
|
Sign up to set email alerts
|

Directivity and Freedom

Abstract: Community-based youth organizations represent potentially powerful settings for activism among marginalized urban youth. This article uses quantitative and qualitative data collected in one such organization to examine the link between youth—adult relationships and youth activism. Survey data point to adults as contributing to youth's activist development and reveal pathways that lead to this outcome. Interview and observation data clarify youth's perceptions of adult support, highlight the complexity of build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…This significant interaction expands previous findings (Kirshner, 2008(Kirshner, , 2009Larson & Hansen, 2005;Larson & Angus, 2011;O'Donoghue & Strobel, 2007;Zeldin, 2004) and suggests that caring and respect for youth's contribution amplifies the effects that AP has on outcomes of the political domain (Kirshner, 2009;O'Donoghue & Strobel, 2007;Zeldin, 2004). This finding confirms previous ones in classroom settings showing that teachers' practices that promoted respect and tolerance were associated with secondary students' disposition to political action, and practices that promoted leadership were associated with students' political efficacy (Martínez & Cumsille, 2010).…”
Section: The Combined Effects Of Relationships and Ap For Sense Of Sosupporting
confidence: 86%
See 4 more Smart Citations
“…This significant interaction expands previous findings (Kirshner, 2008(Kirshner, , 2009Larson & Hansen, 2005;Larson & Angus, 2011;O'Donoghue & Strobel, 2007;Zeldin, 2004) and suggests that caring and respect for youth's contribution amplifies the effects that AP has on outcomes of the political domain (Kirshner, 2009;O'Donoghue & Strobel, 2007;Zeldin, 2004). This finding confirms previous ones in classroom settings showing that teachers' practices that promoted respect and tolerance were associated with secondary students' disposition to political action, and practices that promoted leadership were associated with students' political efficacy (Martínez & Cumsille, 2010).…”
Section: The Combined Effects Of Relationships and Ap For Sense Of Sosupporting
confidence: 86%
“…For example, Larson and Hansen (2005) found that adult partners’ provision of training experiences expanded the capacity to exercise agency in participants of an activist organization. Similarly, O’Donoghue and Strobel (2007) reported that adult provision of feedback bolstered youths’ sense of efficacy. Together, these findings suggest that emotional support, instrumental support, and personalized feedback during the execution of activities are key dimensions of the relationships established between organization members that account for positive youth outcomes.…”
Section: The Organizational Context Of Youth Participationmentioning
confidence: 98%
See 3 more Smart Citations